Object Following Robot berbasis Pembacaan Jarak menggunakan Metode PID Controller - Dyas Restu Palupi; Dahnial Syauqy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Most human activities are carried out by hand. These activities can be well carried out if the items we carry are sufficient in the capacity of our hands, both in quantity and weight. But if the items we carry are too many or large, the activity will be difficult. To solve this problem, we need a system that is able to make these activities easier. In this research, a robot is designed to follow a human. This robot is called object following robot. Using this robot, humans can carry things hands-free. The working principle of the robot is to detect the object by using a proximity sensor and to keep the robot's distance from the object using the PID controller. The robot uses three ultrasonic sensors HC-SR04 as its proximity sensors. These sensors are placed in front, right front, and left front of the robot. Data from the sensor is processed using a PID controller embedded in arduino uno. The output generated from the PID controller is a PWM that will be connected to a DC motor. Meanwhile, to determine the direction of movement of the robot used condition selection from three sensors. Based on the test results, the robot can keep a distance from the object and follow the movement of the object. The settling time (ts) of this robot with a set point of 35 cm is about 1 second. The test result shows that the robot works well, with a relatively fast response time.